Evaluasi Kelaikan Teknis Hunian Vertikal Berdasarkan Permen PUPR No. 22 Tahun 2018 (Studi Kasus: Rusunawa Kraton Kota Tegal) - Pranitasari, Deanty; wibowo, kartono; sumirin, sumirin (Jurnal Kajian Ruang, 2026)
ABSTRACTThe provision of vertical housing in developing cities such as Tegal faces challenges not only in construction but also in sustaining building functionality and maintenance over time. The feasibility of public rental housing (Rusunawa) constitutes a critical component of urban housing asset management to ensure safety, comfort, and service sustainability for low-income residents. This study aims to assess the feasibility level of Block B of Kraton Rusunawa within a framework that integrates technical evaluation and occupants’ perceptions. A descriptive quantitative approach was employed through checklist-based observations in accordance with the Regulation of the Ministry of Public Works and Housing (Permen PUPR No. 22/2018), combined with user assessments. The evaluation covered three main aspects: structure (45%), architecture (35%), and utilities (20%), using a 1–4 rating scale. The results indicate that all floors fall into the conditionally feasible category, with scores ranging from 1.61 to 2.12. A disparity in building conditions across floors was identified, with the fourth and fifth floors exhibiting higher levels of degradation compared to the lower floors, thereby requiring priority maintenance. These findings highlight the importance of preventive maintenance strategies and periodic rehabilitation scheduling as part of Rusunawa asset management. From a policy perspective, the study provides an evaluative basis for local governments in planning maintenance programs and allocating housing budgets within the framework to ensure the long-term sustainability of vertical housing.Keywords: Building Feasibility, Vertical Housing, Public Housing Maintenance, Urban Asset Management, Technical EvaluationABSTRAKPenyediaan hunian vertikal di kota sedang berkembang seperti Kota Tegal menghadapi tantangan tidak hanya pada pembangunan, tetapi juga pada keberlanjutan fungsi dan pemeliharaan bangunan. Kelaikan bangunan Rusunawa menjadi bagian penting dalam manajemen aset permukiman perkotaan untuk menjamin keselamatan, kenyamanan, dan keberlanjutan pelayanan hunian bagi masyarakat berpenghasilan rendah. Penelitian ini bertujuan menilai tingkat kelaikan Gedung Blok B Rusunawa Kraton dalam kerangka evaluasi teknis dan persepsi penghuni. Pendekatan yang digunakan adalah kuantitatif deskriptif melalui observasi berbasis daftar simak sesuai Permen PUPR No. 22 Tahun 2018 yang diintegrasikan dengan penilaian pengguna. Evaluasi dilakukan terhadap tiga aspek utama, yaitu struktur (45%), arsitektur (35%), dan utilitas (20%) menggunakan skala 1–4. Hasil menunjukkan seluruh lantai berada pada kategori laik bersyarat dengan skor antara 1,61 hingga 2,12. Ditemukan disparitas kondisi antar lantai, di mana lantai 4 dan 5 menunjukkan tingkat degradasi lebih tinggi dibanding lantai bawah, sehingga memerlukan prioritas pemeliharaan. Temuan ini menunjukkan pentingnya strategi pemeliharaan preventif dan penjadwalan rehabilitasi berkala sebagai bagian dari pengelolaan aset Rusunawa. Secara kebijakan, hasil penelitian ini memberikan dasar evaluatif bagi pemerintah daerah dalam perencanaan pemeliharaan dan pengalokasian anggaran perumahan agar keberlanjutan hunian vertikal tetap terjamin.Kata Kunci: Kelaikan Bangunan, Hunian Vertikal, Pemeliharaan Perumahan Publik, Manajemen Aset Perkotaan, Evaluasi Teknis